History and Development of Social Entrepreneurship - Abdul Kadir, Mohd Ali Bahari; Mhd. Sarif, Suhaimi (Kulliyyah of Economics and Management Sciences, IIUM, 2021)
This chapter narrates the historical and development of social entrepreneurship through the emergence and mainstreaming of social entrepreneurship. The study argued that there are several reasons for the emergence of social entrepreneurship. Firstly, the growing demands for effective, innovative and sustainable solutions to deal with the complexity of social problems. Secondly, it becomes a duty to give a relief from many social illnesses. Thirdly, the growing array of service areas not addressed by the public sector but failed to attract the private sector.